Analisis Faktor Keberadaan Vektor Penular DBD Melalui Identifikasi Tempat Potensial Perkembangbiakan Nyamuk Aedes Sp. di Desa Gergunung, Kabupaten Klaten, Jawa Tengah - Nur Alvira Pascawati; Ellen Petra Songjanan; Elisabeth Deta; Tri Baskoro Tunggul Satoto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2018)
The presence of potential breeding places can be used to measure the risk of DHF transmission in Klaten. This result can be used by the community to eridication of mosquito breeding place on terget and can improve to early warning system through effective methods for vector control. Type of study was analytic with cross-sectional study. The study was conducted in 104 households with simple random sampling technique. Data analysis used three stages: univariate, bivariate (Chi-square, Kolmogorov Smirnov, Spearman rank) and multivariate test with α=5%. The density of larvae based on the value of CI, HI, and BI amounted to 1.6%, 19.2%, 27.9%. The potential place for larvae breed based on Maya Index of 76%. Containers of open wells with groundwater sources, the volume of water is more than 1 liter and the material from cement can be the preferred place for mosquitoes to breed. Multivariate analysis shows that open wells are strongly related and has a risk of 1,556 (CI: 1,199-2,019) increasing the density of larvae compared with other variables.The density of larvae based on BI is a high category, HI is a moderate category and CI is a low category. This condition is influenced by the presence of open wells made of cement and can hold water in large quantities. Improve to early warning system of DHF transmission through identification of the presence of potential breading places in this area are to close the wells at the household level and conduct regular monitoring on the Controllable Sites.